Analisis Kesediaan Berbagi Identitas Digital Berdasarkan PMT: Faktor Self-Efficacy, Response Efficacy, dan SNS Experience - Hanum Dwi Rosidi; Diah Priharsari; Buce Trias Hanggara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The growth of the internet has led to a large number of users participating in various global online. Social Networking Sites (SNS) are virtual platforms that allow users ito interact with each other, participate in various social and collect information about other site members. Protection motivation theory (PMT) or protection motivation theory is a theory that explains how a person's situation manages his behavior when experiencing risk. This study aims to determine the effect of self-efficacy and efficacy responses on privacy information concerns and also to determine user privacy information concerns about their availability in various digital identities on SNS, and to find out whether there are differences between the experience of using social networks and their willingness to share identities digitally. This study used the CB-SEM method by distributing questionnaires to users of social networks and getting 309 respondents. After testing the hypothesis, it was found that one hypothesis was rejected (not accepted), namely that there was a difference between SNS experience and willingness to share digital identities because it had P-Value of 0.239. In this case, users are not necessarily willing to share their digital identities even though users have long or little experience in social networking.